Owl monkeys Aotus spp in the wild and in captivity - Fernandez Duque, Eduardo (2012)
Owl monkeys Aotus spp have the potential to be a great model to accomplish a thorough integration of zoo and field research. Their most salient features are their nocturnal habits, monogamous social organization and paternal care, features that should make them of interest to the public. Following a brief historical perspective on our knowledge of owl monkey biology, I describe in detail, drawing from research with both captive and wild animals, those aspects that make owl monkeys unusual among primates and mammals. First, owl monkeys are the only anthropoids with nocturnal habits, and the study of their remarkable activity patterns has benefited enormously from an integrated approach that combined field research with research in semi‐natural conditions and the laboratory. Second, up until recently, our understanding of social monogamy and the involvement of the ♂♂ in infant care, two defining characteristics of the genus, have been primarily informed by studies of captive individuals. In the future, a truly integrated laboratory–field approach that focuses on certain areas that cannot be examined in only one or the other setting (e.g. reproductive biology, communication, energetics) will offer unique opportunities for synergistic interactions between zoo and field research that will have both intellectual and practical benefits.